Factory air raid shelter, 1940-1945
1945 1939-1945 "Factory air raid shelter, 1940-1945" [hfr0160], 1940-1945 For air raid protection, huge shelters had to be built at every large workplace. These underground shelters are at the New Southgate, North London works of Standard Telephones and Cables Ltd., where 10,500 people were working by the end of the war.